2019
DOI: 10.1108/ci-07-2018-0056
|View full text |Cite
|
Sign up to set email alerts
|

The potency of recycled aggregate in new concrete: a review

Abstract: Purpose This paper aims to review the effect of using recycled aggregates (RA) on the properties of recycled aggregate concrete (RAC) following the steady rise in global demand for concrete and the large generation of construction and demolition waste. Design/methodology/approach This study reviewed relevant literature of research work carried out by previous researchers, leading to a deeper understanding of the properties of both RA and RAC. The properties of RA and RAC reported in the various studies were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 89 publications
0
9
0
Order By: Relevance
“…e main components of construction waste are bricks and concrete blocks [2][3][4][5]. In recent years, many studies have been focused on investigating the properties and reuse methods of waste concretes, and correspondingly the recycling rate of waste concretes is high [6][7][8][9][10]. Researches on waste bricks have been limited to their applications as recycled aggregate, or the effect of waste brick powder content on the performance of cement-based materials [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…e main components of construction waste are bricks and concrete blocks [2][3][4][5]. In recent years, many studies have been focused on investigating the properties and reuse methods of waste concretes, and correspondingly the recycling rate of waste concretes is high [6][7][8][9][10]. Researches on waste bricks have been limited to their applications as recycled aggregate, or the effect of waste brick powder content on the performance of cement-based materials [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Concrete is an essential construction material. However, the production of concrete causes huge environmental challenges arising from aggregates and cement requirements [1,2].…”
Section: Introductionmentioning
confidence: 99%
“…Fathifazl et al [5] also argued that the devastating effect of RA on the elastic modulus of RAC has not been salvaged by any known mix design technique except the equivalent mortar volume (EMV) approach. Thus, in a review carried out, Anike et al [1] concluded that factors such as grade and composition of parent concrete, mixing method, content and moisture condition of RA, and presence of admixtures definitely influence the properties of RAC as reflected in the results available in literature.…”
Section: Introductionmentioning
confidence: 99%
“…Recycling of concrete waste remains an important step in the pursuit of global environmental sustainability [1]. This is because, the use of recycled aggregates (RA) not only saves the diminishing natural resources but also offers a relief to the pressure imposed on landfills [2].…”
Section: Introductionmentioning
confidence: 99%